How Walkable Neighborhoods Promote Physical Activity: Policy Implications for Development and Renewal. (October 2020) - Balcetis, Emily; Cole, Shana; Duncan, Dustin T.
Mitigating physical inactivity is vital for public health. Neighborhoods that include visually engaging, eye-catching objects and locations increase the frequency, duration, and vigorousness of resident and visitors' exercise. Three findings are key: First, individuals in neighborhoods that include features directly relevant to exercise—including dense mixed-use developments, greenspaces, parks, sidewalks, and connected streets—are more active and maintain better health. Second, when neighborhoods include visually interesting contents that are indirectly relevant to exercise, individuals believe exercise is more feasible, and this change in psychological mindset predicts increased physical activity. Third, as individuals become more physically active, they are less tempted by unhealthy food, which may counteract the detrimental effects on healthy eating that having proximal fast-food restaurants in neighborhoods poses. Race and socioeconomic disparities co-exist with the contents of neighborhoods. We highlight implications for urban planners, developers, community groups, and individuals selecting and designing public spaces that are conducive to healthy lifestyles.